Causal links between circulatory inflammatory cytokines and risk of digestive polyps: a Mendelian randomization analysis - Yan, Ziqi; Zheng, Hongming; Feng, Jieni; Li, Yiting; Hu, Zhifan; Wu, Yuan; Liao, Guibin; Miao, Taosheng; Qiu, Zexin; Mo, Qiaolan; Li, Jia; Lai, Ailin; et al. (Frontiers in Pharmacology, 2024)
Background: There is a high morbidity of polyps in the digestive tract, and certain subtypes of polyps are thought to induce cancer progression and often recur, which may be associated with chronic inflammation. Mendelian randomization (MR) can help identify potential causative relationships and inform early treatment action.We performed a bidirectional two-sample MR analysis implementing the results from genome-wide association studies for 41 serum cytokines from 8,293 Finnish individuals, and three types of polyps from European ancestry, respectively, including gastric polyp (6,155 cases vs 341,871 controls), colonic polyp (22,049 cases vs 332,368 controls) and gallbladder polyp (458 cases vs 340,083 controls). Inverse-variance weighted (IVW), weight median (WM), and MR-Egger methods were used for calculating causal estimates. Furthermore, Bayesian model averaging MR (MR-BMA) method was employed to detect the dominant causal circulatory cytokines with adjustment for pleiotropy effects. Results: Our univariable MR using inverse-variance weight method identified causal associations